2019
DOI: 10.1126/sciadv.aax0698
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin/Tcf7l2–dependent transcriptional regulation of GLUT1 gene expression by Zic family proteins in colon cancer

Abstract: The zinc finger of the cerebellum (ZIC) proteins has been implicated to function in normal tissue development. Recent studies have described the critical functions of Zic proteins in cancers and the potential tumor-suppressive functions in colon cancer development and progression. To elucidate the functional roles of Zic proteins in colorectal cancer, we knocked out the Zic5 gene and analyzed the chromatin localization pattern and transcriptional regulation of target gene expression. We found that Zic5 regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 60 publications
(70 reference statements)
1
38
0
Order By: Relevance
“…Further, the present study revealed that the silencing of β‐catenin could reverse the upregulation of GLUT1 caused by the silencing HDAC4. It has also been previously suggested that the Wnt/β‐catenin pathway exerts its effects on colorectal cancer cells through mediating GLUT1 33 . GLUT1 has been highlighted to be a downstream glycolytic target gene of β‐catenin signaling, and they share a positive correlation in expression 34 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, the present study revealed that the silencing of β‐catenin could reverse the upregulation of GLUT1 caused by the silencing HDAC4. It has also been previously suggested that the Wnt/β‐catenin pathway exerts its effects on colorectal cancer cells through mediating GLUT1 33 . GLUT1 has been highlighted to be a downstream glycolytic target gene of β‐catenin signaling, and they share a positive correlation in expression 34 .…”
Section: Discussionmentioning
confidence: 98%
“…It has also been previously suggested that the Wnt/β-catenin pathway exerts its effects on colorectal cancer cells through mediating GLUT1. 33 GLUT1 has been highlighted to be a downstream glycolytic target gene of β-catenin signaling, and they share a positive correlation in expression. 34 Moreover, inhibition of TUG1 was found to competitively bind to miR-145-5p to target Bnip3 and inactivate the Wnt/β-catenin signaling pathway, hence alleviating the myocardial cell injury induced by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…38 A recent study revealed that Zic5 could suppress the transcription of GLUT1 in a β-catenin/TCF4-dependent manner to downregulate glucose uptake in HCT116 colon cancer cells, while Zic2 played a completely opposite role. 39 However, Zic1 and Zic4 were highly expressed through promoter DNA demethylation in desmoid tumor, 40 which is another type of tumor with irregular activation of the Wnt signaling. 41 These studies indicate that the function of Zic family differs greatly among tumor histological types.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more researches demonstrated that aerobic glycolysis plays a pivotal role in the development of colon cancer and in the treatment of colon cancer by using anticancer agent [34][35][36]. However, it is not clear whether IC261 are involved in the regulation of aerobic glycolysis in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%